PEMILIHAN INVESTASI KELUARGA UNTUK MENINGKATKAN EKONOMI KECIL DAN MENENGAH DENGAN MENGGUNAKAN AHP - Misbahul Munir (Journal of Research and Technology, 2017)
Financial management has an important role in a small family. Many mistakes made in the conduct of investment by a family, it rose doubts in investing. It is necessary to understand to many criterias, so it can be determined the type of investment that appropriate with the family financial conditions. The method used in this research is the Analytic Hierarchy Process (AHP). AHP is used in order to reduce subjectivity of decision-makers. The alternatives in this study are Savings, Gold Investment, Stocks, Insurance, and Property. To optimize the family's investment, it is necessary to make a ranking priority. The ranking was based on five criterias: Economic of Family, Benefit Investment, Operational, Legal, and Syariah Aspect. Based on the alternatives andcriteria and also sub-criteria, the decision of hierarchical model were created. According to experts, the comparison between four criterias and sub-criterias were assessed. The comparison was then tested for consistency. Data were processed using Expert Choice software version 11. The final result is priority ranking of the purchasing property investment with a weight point of 0,313.